The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997000200012
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the hippocampus, amygdala, entorhinal cortex and posterior parietal cortex in memory consolidation

Abstract: A total of 182 young adult male Wistar rats were bilaterally implanted with cannulae into the CA1 region of the dorsal hippocampus and into the amygdaloid nucleus, the entorhinal cortex, and the posterior parietal cortex. After recovery, the animals were trained in a stepdown inhibitory avoidance task. At various times after training (0, 30, 60 or 90 min) the animals received a 0.5-µl microinfusion of vehicle (saline) or 0.5 µg of muscimol dissolved in the vehicle. A retention test was carried out 24 h after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
(45 reference statements)
4
10
0
2
Order By: Relevance
“…The findings establish an important advance in the ability to discover the temporal relationships between emotional arousal and the modulation of memory consolidation as well as set the stage for future experiments to use optogenetic inhibition in combination with other techniques. The data from the ArchT experiments are consistent with previous studies showing that BLA inactivation impairs retention for learning (33,34), although it should be noted that the CAG promoter is a general cellular promoter, limiting interpretation of the findings based on specific cell type. However, these previous studies were unable to determine the temporal window in which emotional arousal led to BLA activation and the subsequent modulation of memory consolidation, despite the need to determine the initiation time and duration of BLA activity for normal memory consolidation.…”
Section: Discussionsupporting
confidence: 86%
“…The findings establish an important advance in the ability to discover the temporal relationships between emotional arousal and the modulation of memory consolidation as well as set the stage for future experiments to use optogenetic inhibition in combination with other techniques. The data from the ArchT experiments are consistent with previous studies showing that BLA inactivation impairs retention for learning (33,34), although it should be noted that the CAG promoter is a general cellular promoter, limiting interpretation of the findings based on specific cell type. However, these previous studies were unable to determine the temporal window in which emotional arousal led to BLA activation and the subsequent modulation of memory consolidation, despite the need to determine the initiation time and duration of BLA activity for normal memory consolidation.…”
Section: Discussionsupporting
confidence: 86%
“…The Kruskal-Wallis ANOVA on the difference scores showed a significant effect of group [H (df ϭ 3; n ϭ 47) ϭ 9.76; p Ͻ 0.05] with a significant difference between the highest dose group and vehicle controls ( p Ͻ 0.01) and between the highest dose group and the lowest dose group ( p Ͻ 0.05). Consistent with previous work Izquierdo et al, 1997;Zanatta et al, 1997), post-training inactivation of the amygdala with muscimol dose-dependently impaired inhibitory avoidance learning. However, unlike the results of Brioni et al (1989), who found effects only at low doses, our results are more consistent with other inhibitory avoidance studies in the literature that found effects using our higher dose Zanatta et al, 1997).…”
Section: Post-training Functional Inactivation Of the Amygdala Impairsupporting
confidence: 91%
“…It is thus likely that the ability to affect one kind of learning and not the other with post-training manipulations of the amygdala reflects differences in the relative complexity of the neural network underlying each type of learning. Indeed, a number of lesion studies have implicated the entorhinal and parietal cortex in late memory phases of inhibitory avoidance learning Zanatta et al, 1997), whereas, for example, Pavlovian fear conditioning is spared after entorhinal cortex lesions (Phillips and LeDoux, 1995). Furthermore, although lesion studies have consistently implicated the amygdala in Pavlovian fear conditioning (LeDoux et al, 1990;Maren et al, 1996a;Maren, 1998), lesions of the amygdala appear to have less clear-cut effects on inhibitory avoidance learning, especially if given after training (Liang et al, 1982;Parent et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it should be kept in mind that, as seen for memory consolidation (Dudai 2004), the systems and cellular processes underlying reconsolidation are likely to differ among different learning paradigms. For example, IA differs from auditory and contextual fear conditioning in the involvement of amygdala and cortical areas during both acquisition and consolidation (Phillips and LeDoux 1995;Izquierdo et al 1997;Zanatta et al 1997;Wilensky et al 2000). These differences likely reflect distinctions in the neuronal networks underlying each type of learning.…”
Section: The Temporally Limited Requirement Of Protein Synthesis and mentioning
confidence: 99%